A qualitative study of parents' perceptions and use of portion size strategies for preschool children's snacks. (1st May 2015) - Blake, Christine E.; Fisher, Jennifer Orlet; Ganter, Claudia; Younginer, Nicholas; Orloski, Alexandria; Blaine, Rachel E.; Bruton, Yasmeen; Davison, Kirsten K.
Highlights: Increases in childhood obesity correspond to shifts in child snack portion sizes. Parents often define child snacks by portion size. Parents consider healthfulness, location, hunger, and timing to portion child snacks. Low-income parents described a diverse set of strategies for portioning child snacks. Understanding of parent portion size decision making and child diet quality is needed. Abstract: Objective: Increases in childhood obesity correspond with shifts in children's snacking behaviors and food portion sizes. This study examined parents' conceptualizations of portion size and the strategies they use to portion snacks in the context of preschool-aged children's snacking. Methods: Semi-structured qualitative interviews were conducted with non-Hispanic white (W), African American (AA), and Hispanic (H) low-income parents (n = 60) of preschool-aged children living in Philadelphia and Boston. The interview examined parents' child snacking definitions, purposes, contexts, and frequency. Verbatim transcripts were analyzed using a grounded theory approach. Coding matrices compared responses by race/ethnicity, parent education, and household food security status. Results: Parents' commonly referenced portion sizes when describing children's snacks with phrases like "something small." Snack portion sizes were guided by considerations including healthfulness, location, hunger, and timing. Six strategies for portioning snacks were presented including use of small containers, subdividing large portions, buying prepackaged snacks, use of hand measurement, measuring cups, scales, and letting children determine portion size. Differences in considerations and strategies were seen between race/ethnic groups and by household food security status. Conclusions: Low-income parents of preschool-aged children described a diverse set of considerations and strategies related to portion sizes of snack foods offered to their children. Future studies should examine how these considerations and strategies influence child dietary quality.